Evaluating the Effects of Replacing Feed Grade Antibiotics with Yeast, Cinnamon, or Zinc Oxide and Copper Sulfate on Nursery Pig Performance - A. Langemeier; J. Morton; S. Scotten; J. L. Nelssen (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 288 weaned pigs (Line 200 × 400; DNA, Columbus, NE; initially 11.8 lb) were used in a 42-d study to compare the effects of feeding antibiotic alternatives (pharmacological trace minerals, copper and zinc, yeast, or essential oils), alone or in combination, on nursery pig performance in replacement to a common antimicrobial agent (carbadox, Mecadox®, Phibro Animal Health, Teaneck, NJ). Pigs were allotted to 1 of 9 dietary treatments in pens of 4 at weaning in a randomized complete block design with 8 replications per treatment. Dietary treatments were arranged with a negative control diet with no medication or other feed additive, a positive control with added carbadox, or 7 treatments including added copper sulfate (CuSO4; 0 vs. 125 ppm Cu) and added zinc oxide (ZnO; 0 vs. 3,000 ppm Zn from d 0 to 7 and 2,000 ppm Zn from d 7 to 28), essential oils from XTRACT 6930 (Capsicum oleoresin2%, carvacrol 5%, cinnamaldehyde 3%, Pancosma North America, Drumondville, Quebec, Canada) at 2 lb/ton, Safmannan A (Yeast cell walls, Lesaffre Yeast Corporation, Milwaukee, WI) at 0.5 lb/ton, and Actisaf HR (yeast cells, Lesaffre Yeast Corporation, Milwaukee, WI) at 1.5 lb/ton. These supplements were fed alone or in combination. From d 0 to 7 experimental diets were a pelleted ration; and fed in a meal form from d 7 to 28, followed by a common corn-soybean meal-based diet without any antimicrobial, pharmacological trace minerals, essential oils, or yeast from d 28 to 42. Essential oils and yeast had no significant (P>0.05) effect on ADG. Feeding carbadox or pharmacological trace minerals (Cu and Zn) improved ADG (P<0.05) of nursery pigs compared to the non-medicated control diet. Carryover effects from any of these dietary treatments on subsequent growth performance were not significantly different (P>0.05). The use of pharmacological trace minerals Cu and Zn alone or in conjunction with either yeast or essential oil allows for competitive ADG and F/G with an antimicrobial agent, like carbadox. In summary, under the conditions of this experiment, pigs fed the combination of zinc and copper had similar growth performance to those fed carbadox (P>0.05).
Keywords: alternative; antibiotic; carbadox; copper; essential oil; nursery pig; pharmacological trace minerals; yeast; zinc